(untitled) (The Pretoria Student Law Review, 2025)
Evans v United Kingdom saw the foundational medico-legal doctrine of informed consent come into conflict with women’s reproductive rights in the context of in-vitro fertilisation. In this matter, the appellant, Evans, appealed the Court of Appeal’s decision to sustain her erstwhile partner’s (Johnston) right to withdraw his consent to implant embryos they had fertilised together. These embryos were Evans’s last opportunity to have genetically related children. Evans submitted that the municipal courts had not adequately considered her position as a woman, and the judgment violated her article 8 and 14 rights under the European Convention of Human Rights. This case note analyses the majority and minority judgments of the European Court of Human Rights (ECHR). It finds that Evans’s and Johnston’s competing interests had to be weighed against each other, since the matter fell within the margin of appreciation awarded to the Grand Chamber of the ECHR. Evans’s rights under articles 8 and 14 were both due consideration, and it was appropriate to attribute significance to her interests as a woman. However, her rights had to be weighed against Johnston’s under article 8 and the importance of reinforcing the doctrine of informed consent. It is concluded that Evans’s interests could not legally outweigh the dangerous precedent that would have been set by finding in her favour. Therefore, although the verdict was unfortunate for Evans, it was correct for the Grand Chamber to rule in favour of the UK to set a sound precedent that protects patient autonomy in Europe.